Positive lithium supplementing material, preparation method thereof, positive plate and lithium ion battery

By evenly distributing carbon nanotubes in the positive electrode lithium supplement material and covering the carbon cladding layer, the problem of low conductivity of the existing positive electrode lithium supplement material is solved, higher conductivity and capacity are achieved, and the stability of the material is improved.

CN119786611APending Publication Date: 2025-04-08CHONGQING TALENT NEW ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411995676.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The current positive electrode lithium supplement material has a low conductivity, which affects its performance of its specific capacity at a lower charging voltage.

Method used

The positive electrode lithium supplement material including carbon nanotubes and carbon cladding layers is adopted. The carbon nanotubes are evenly distributed in the lithium supplement matrix, and the carbon cladding layer is coated on part of the core to improve the conductive properties of the material.

Benefits of technology

The conductive performance and capacity of the positive electrode lithium supplement material is significantly improved, the air sensitivity is reduced, and the capacity decreases slowly after being left in the air and the phase structure is stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224481800000091
    Figure BDA0005224481800000091
  • Figure BDA0005224481800000101
    Figure BDA0005224481800000101
  • Figure HDA0005224481810000011
    Figure HDA0005224481810000011
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly discloses a positive electrode lithium supplement material and a preparation method thereof, a positive plate and a lithium ion battery, the positive electrode lithium supplement material comprises: an inner core, the inner core comprises a lithium supplement matrix and carbon nanotubes, the carbon nanotubes are dispersed in the lithium supplement matrix; the carbon coating layer is coated on at least part of the surface of the inner core. Therefore, the positive electrode lithium supplementing material has excellent conductivity, and the available energy of the lithium ion battery adopting the positive electrode lithium supplementing material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a positive electrode lithium supplement material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] When lithium-ion batteries are charged for the first time, there will inevitably be processes such as the formation of SEI film, the shedding of negative electrode material particles, and the irreversible deposition of lithium metal, which consume active lithium ions from the positive electrode material, resulting in a reduction in the available energy of the battery. The irreversible capacity loss of the most widely used graphite negative electrode is >6%, while for silicon-based and tin-based alloy negative electrodes with high specific capacity, the irreversible capacity loss is even as high as 10% to 20%. Pre-lithiation technology includes negative electrode pre-lithiation and positive electrode lithium replenishment. Although the current positive electrode lithium replenishment materials can replenish lithium to a certain extent, the conductivity of the positive electrode lithium replenishment materials is low, which affects its gram-to-gram capacity at a lower charging voltage. Therefore, the current positive electrode lithium replenishment related technologies still need to be improved. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a positive electrode lithium supplement material with excellent conductivity or a wide range of applications, a preparation method thereof, a positive electrode sheet and a lithium ion battery.

[0004] In a first aspect, the present application proposes a positive electrode lithium supplement material, comprising: a core, comprising a lithium supplement matrix and carbon nanotubes, wherein the carbon nanotubes are dispersed in the lithium supplement matrix; and a carbon coating layer, which is coated on at least part of the surface of the core. Thus, the positive electrode lithium supplement material has good electrical conductivity.

[0005] In some embodiments, the carbon nanotubes are evenly distributed in the lithium supplement matrix, thereby further improving the conductivity of the positive electrode lithium supplement material.

[0006] In some embodiments, the thickness of the carbon coating layer is 5 nm to 10 nm, thereby further improving the conductivity of the positive electrode lithium supplement material.

[0007] In some embodiments, the carbon coating layer includes carbon nanoparticles.

[0008] In some embodiments, the lithium-supplemented matrix includes Li2NiO2, Li2MoO3, Li5Fe 0.9 Al 0.1 O4, Li6MnO4, Li6Mn 0.5 Ru 0.5 At least one of O4, Li5FeO4, Li6CoO4, and Li3N. Thus, the material sources are wide and the lithium-supplemented matrix can be selected in a wide range.

[0009] In some embodiments, the mass ratio of the lithium-supplementing matrix to the carbon nanotubes is 1:0.01-0.5. Thus, the conductivity of the lithium-supplementing matrix can be effectively improved without substantially affecting the lithium-supplementing performance of the lithium-supplementing material.

[0010] In some embodiments, the D50 particle size of the positive electrode lithium supplement material is 6 μm to 15 μm, so that it can cooperate with the positive electrode material to improve the performance of the lithium-ion battery using the positive electrode lithium supplement material.

[0011] The second aspect of the present application proposes a method for preparing a positive electrode lithium replenishing material, comprising: mixing a lithium replenishing matrix and carbon nanotubes to obtain a core precursor; mixing the core precursor with a carbon source and performing a first sintering under a protective atmosphere to obtain the positive electrode lithium replenishing material; the positive electrode lithium replenishing material comprises a core and a carbon coating layer, the core comprising a lithium replenishing matrix and carbon nanotubes dispersed in the lithium replenishing matrix, and the carbon coating layer is coated on at least a portion of the surface of the core.

[0012] The above method of the present application has a simple operation process and is easy to realize industrial production, and the prepared positive electrode lithium supplement material has excellent conductive properties.

[0013] In some embodiments, preparing the core precursor includes: before mixing the lithium-supplemented matrix with carbon nanotubes, first grinding the lithium-supplemented matrix, thereby making the lithium-supplemented matrix have a smaller particle size, which is conducive to uniform dispersion of carbon nanotubes in the lithium-supplemented matrix.

[0014] In some embodiments, the preparation of the core precursor includes: mixing the lithium-supplementing matrix, carbon nanotubes and solvent, and performing a second grinding on the obtained mixture to obtain a mixed slurry; and spray drying the mixed slurry to obtain the core precursor. Thus, the lithium-supplementing matrix and the carbon nanotubes can be uniformly mixed to obtain a positive electrode lithium-supplementing material with better conductive properties.

[0015] In some embodiments, the solvent includes at least one of ethanol, methanol, and ethylene glycol. Thus, the material source is wide and the cost is low.

[0016] In some embodiments, the carbon source includes at least one of sucrose, glucose, SUPER-P, KS-6, KS-15, VGCF, and SFG6. Thus, the carbon source can be selected from a wider range and the cost is lower.

[0017] In some embodiments, the core and the carbon source are mixed in a mass ratio of 1:0.01 to 0.5, which is beneficial to improving the overall conductivity of the positive electrode lithium supplement material.

[0018] In some embodiments, the first sintering atmosphere is a nitrogen atmosphere.

[0019] In some embodiments, the first sintering temperature is 350°C to 500°C.

[0020] In some embodiments, the first sintering time is 2 hours to 5 hours.

[0021] Under the above sintering conditions, it is conducive to forming a carbon coating layer on the surface of the inner core, thereby improving the conductivity of the surface of the positive electrode lithium supplement material.

[0022] The third aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode material layer located on at least one side of the positive electrode current collector, wherein the positive electrode material layer comprises the positive electrode lithium replenishing material described in the first aspect of the present application or the positive electrode lithium replenishing material prepared by the method described in the second aspect of the present application. Thus, the positive electrode sheet has good electrical conductivity.

[0023] The fourth aspect of the present application provides a lithium-ion battery, comprising the positive electrode lithium-supplementing material described in the first aspect of the present application, the positive electrode lithium-supplementing material prepared by the method described in the second aspect of the present application, or the positive electrode sheet described in the third aspect of the present application. Thus, the lithium-ion battery has good conductivity and high available capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the first charging curve of the battery assembled with the positive electrode lithium supplement material prepared in Example 1 of the present application.

[0025] Figure 2 This is the first charging curve of the battery assembled with the positive electrode lithium supplement material prepared in Example 4 of the present application.

[0026] Figure 3 This is the first charging curve of the battery assembled with the positive electrode lithium supplement material prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0027] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.

[0028] The first aspect of the present application proposes a positive electrode lithium supplement material, including a core and a carbon coating layer coated on at least part of the surface of the core, wherein the core includes a lithium supplement matrix and carbon nanotubes, and the carbon nanotubes are dispersed in the lithium supplement matrix. The present application disperses carbon nanotubes inside the lithium supplement matrix, and forms a carbon coating layer on the surface of the lithium supplement matrix, thereby forming an internal-surface carbon conductive channel, and the carbon coating layer can stabilize the surface structure of the material, thereby improving the overall conductivity of the positive electrode lithium supplement material. Among them, the carbon nanotube has a high specific surface area, can provide more active sites, so that electrons can be quickly transferred on the surface of the carbon nanotube, reduce resistance, and improve energy conversion efficiency; the carbon coating layer can form a better conductive channel with the carbon nanotubes dispersed in the core, thereby improving the overall conductivity of the positive electrode lithium supplement material, and the carbon coating layer can stabilize the surface structure of the positive electrode lithium supplement material, which is conducive to improving the capacity of the positive electrode lithium supplement material, and can also reduce air sensitivity. After being placed in the air, the capacity of the positive electrode lithium supplement material decreases slowly, and the phase structure of the positive electrode lithium supplement material does not change significantly.

[0029] In some embodiments, the carbon nanotubes are evenly distributed in the lithium supplement matrix, thereby further improving the conductivity of the positive electrode lithium supplement material.

[0030] It can be understood that the description method "uniform distribution" used in this article should be understood in a broad sense, which can mean that the carbon nanotubes are completely uniformly distributed in the lithium-supplemented matrix, and also allows the concentration of carbon nanotubes at different positions in the lithium-supplemented matrix to fluctuate within a reasonable range, such as a reasonable error.

[0031] In some embodiments, the thickness of the carbon coating layer is 5nm to 10nm, for example, 5nm, 6nm, 7nm, 8nm, 9nm or 10nm, etc. It can be understood that within the above thickness range, it is beneficial to improve the conductivity of the surface of the positive electrode lithium supplement material and stabilize the surface structure. If the carbon coating layer is too thick, it may be easy to fall off, and if the carbon coating layer is too thin, the coating effect is not good, the coating is uneven, and the effect of stabilizing the surface structure is relatively poor, and it is not conducive to improving the conductivity of the positive electrode lithium supplement material.

[0032] In some embodiments, the carbon coating layer includes carbon nanoparticles, thereby further improving the conductivity and capacity of the positive electrode lithium supplement material and maintaining the stability of the positive electrode lithium supplement material.

[0033] In some embodiments, the lithium-supplemented matrix includes Li2NiO2, Li2MoO3, Li5Fe 0.9 Al 0.1 O4, Li6MnO4, Li6Mn 0.5 Ru 0.5At least one of O4, Li5FeO4, Li6CoO4, and Li3N. Thus, the material sources are wide and the lithium-supplemented matrix can be selected in a wide range.

[0034] In some embodiments, the mass ratio of the lithium supplement matrix to the carbon nanotubes is 1:0.01-0.5, specifically 1:0.01, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, etc. Thus, the conductivity of the lithium supplement matrix can be effectively improved, and the performance of the lithium supplement performance of the lithium supplement material will not be affected. If the mass ratio of the lithium supplement matrix to the carbon nanotubes is too high, the conductivity and electron transfer efficiency of the positive electrode material will be relatively reduced. If the mass ratio of the lithium supplement matrix to the carbon nanotubes is too low, the specific capacity and specific energy of the positive electrode material may be reduced.

[0035] In some embodiments, the D50 particle size of the positive electrode lithium supplement material is 6μm to 15μm, such as 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc. Thus, it can cooperate with the positive electrode material to improve the performance of the lithium-ion battery using the positive electrode lithium supplement material. If the D50 particle size of the positive electrode lithium supplement material in this application is too small, the specific surface area of ​​the particle material is large, and it is easy to react with the electrolyte, resulting in increased internal resistance and temperature, which may cause safety hazards. Although the initial capacity of the lithium supplement material is high, the irreversible capacity is also large, resulting in decreased cycle performance; if the D50 particle size of the positive electrode lithium supplement material is too large, the initial capacity of the positive electrode material will be relatively low, and the cycle performance will be relatively good.

[0036] The second aspect of the present application proposes a method for preparing a positive electrode lithium supplement material, comprising:

[0037] S1: mixing the lithium-supplemented matrix and the carbon nanotubes to obtain a core precursor.

[0038] In this step, there is no particular limitation on the manner of mixing the lithium-supplemented matrix and the carbon nanotubes, as long as they can be mixed evenly and the carbon nanotubes are dispersed in the lithium-supplemented matrix.

[0039] In some embodiments, before mixing the lithium-supplement matrix with the carbon nanotubes, the lithium-supplement matrix may be first ground to obtain lithium-supplement matrix nanoparticles, and then the obtained lithium-supplement matrix nanoparticles and carbon nanotubes may be mixed. Thus, the lithium-supplement matrix may have a smaller particle size, which is conducive to uniform dispersion of the carbon nanotubes in the lithium-supplement matrix.

[0040] In some embodiments, the lithium-supplementing matrix, carbon nanotubes and solvent can be mixed, and the obtained mixture can be subjected to a second grinding to obtain a mixed slurry; the mixed slurry can be spray-dried to obtain the core precursor. In this way, the lithium-supplementing matrix and carbon nanotubes can be evenly mixed to obtain a positive electrode lithium-supplementing material with better conductivity. Among them, spray drying has a fast speed, good product quality and high uniformity, and the drying conditions can be strictly controlled, while the time period of ordinary drying is long and it is not easy to control the environment.

[0041] As a specific example, the lithium supplement matrix can be firstly ground to obtain lithium supplement matrix nanoparticles, and then the lithium supplement matrix nanoparticles, carbon nanotubes and solvent are mixed and secondly ground to obtain a mixed slurry, and then the mixed slurry is spray-dried. Thus, a positive electrode lithium supplement material in which carbon nanotubes are substantially uniformly distributed in the lithium supplement matrix can be obtained.

[0042] In some embodiments, the lithium-supplemented matrix nanoparticles and the carbon nanotubes are mixed in a mass ratio of 1:0.01 to 0.5, for example, the mass ratio may be 1:0.01, 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4 or 1:0.5. Within the above mass ratio range, it is beneficial to reduce the waste of a certain raw material while improving the conductive performance.

[0043] In some embodiments, the solvent includes at least one of ethanol, methanol, and ethylene glycol. Thus, the material source is wide and the cost is low.

[0044] In this step, the specific method of the first grinding is not particularly limited and can be selected according to actual conditions. For example, the lithium-supplemented matrix can be put into a ball mill for ball milling to obtain lithium-supplemented matrix nanoparticles of smaller size.

[0045] In some embodiments, the specific operation of the second grinding is not particularly limited, as long as the lithium-supplemented matrix nanoparticles, carbon nanotubes and solvent can be fully mixed and the carbon nanotubes are dispersed into the lithium-supplemented matrix nanoparticles, such as but not limited to ball milling.

[0046] In some embodiments, preparing the lithium-supplemented matrix comprises:

[0047] S10: Mixing an iron source and a lithium source and ball milling to obtain a first mixture.

[0048] In some embodiments, the molar mass ratio of the lithium source to the iron source is 5 to 30: 1, for example, 5: 1, 10: 1, 15: 1, 20: 1, 25: 1 or 30: 1, etc. In some specific examples, the molar mass ratio of the lithium source to the iron source is 5.5: 1. Within the above molar mass ratio range, it is conducive to sufficient ball milling and reduce the waste of raw materials.

[0049] In some embodiments, the iron source includes at least one of ferric oxide, ferrosinic oxide, ferric oxyhydroxide, ferric nitrate and ferric citrate; in some specific examples, the iron source is ferric oxide.

[0050] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide monohydrate, anhydrous lithium hydroxide and lithium oxide; in some specific examples, the lithium source is lithium oxide.

[0051] S20: performing a second sintering on the first mixture under an inert atmosphere to obtain the lithium-supplemented matrix.

[0052] In this step, the first mixture can be loaded into a corrosion-resistant crucible and placed in a furnace for sintering, and the atmosphere in the furnace is nitrogen or argon; the sintered material is crushed and sieved to obtain a lithium-supplemented matrix.

[0053] In some embodiments, the second sintering includes: in the inert atmosphere, heating to a first sintering temperature at a first preset heating rate for a first sintering; in the inert atmosphere, heating to a second sintering temperature at a second preset heating rate for a second sintering.

[0054] In some embodiments, the first preset heating rate is 1°C / min to 15°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0055] In some embodiments, the temperature of the first sintering stage is 300°C to 600°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C; in some specific examples, the temperature of the first sintering stage is 500°C.

[0056] In some embodiments, the sintering time is 1 h to 70 h, for example, 1 h, 5 h, 10 h, 20 h, 30 h, 40 h, 50 h, 60 h or 70 h, etc.; in some specific examples, the sintering time is 4 h.

[0057] In some embodiments, the second preset heating rate is 1°C / min to 15°C / min, for example, it can be 1°C / min, 2°C / min, 4°C / min, 6°C / min, 8°C / min, 10°C / min, 12°C / min or 15°C / min.

[0058] In some embodiments, the temperature of the second stage sintering is 800°C to 100°C, for example, 800°C, 850°C, 900°C, 950°C or 1000°C; in some specific examples, the temperature of the second stage sintering is 900°C.

[0059] The second-stage sintering time is 1 h to 70 h, for example, 1 h, 5 h, 10 h, 20 h, 30 h, 40 h, 50 h, 60 h or 70 h, etc.; in some specific examples, the second-stage sintering time is 20 h.

[0060] Within the above sintering conditions, it is beneficial to increase the sintering rate and improve the quality of the lithium-supplemented matrix.

[0061] S2: Mixing the core precursor with a carbon source and performing a first sintering under a protective atmosphere to obtain the positive electrode lithium replenishing material; the positive electrode lithium replenishing material includes a core and a carbon coating layer, the core includes a lithium replenishing matrix and carbon nanotubes dispersed in the lithium replenishing matrix, and the carbon coating layer is coated on at least a portion of the surface of the core.

[0062] In some embodiments, the carbon source includes at least one of sucrose, glucose, SUPER-P, KS-6, KS-15, VGCF, and SFG6. Thus, the carbon source can be selected from a wider range and the cost is lower.

[0063] In some embodiments, the core precursor and the carbon source are mixed at a mass ratio of 1:0.01 to 0.5, for example, the mass ratio may be 1:0.01, 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.4 or 1:0.5. Within the above mass ratio range, it is beneficial to obtain a carbon coating layer with good wrapping effect and appropriate thickness, thereby improving the overall conductivity of the positive electrode lithium supplement material.

[0064] In some embodiments, the first sintering atmosphere is a nitrogen atmosphere.

[0065] In some embodiments, the first sintering temperature is 350°C to 500°C, for example, 350°C, 400°C, 450°C or 500°C.

[0066] In some embodiments, the first sintering time is 2 hours to 5 hours, for example, 2 hours, 3 hours, 4 hours or 5 hours.

[0067] Under the above sintering conditions, it is conducive to forming a carbon coating layer on the surface of the inner core, thereby improving the conductivity of the surface of the positive electrode lithium supplement material.

[0068] The present application fills carbon nanotubes inside the positive electrode lithium replenishing material, and carbon nanoparticles are coated on the surface of the positive electrode lithium replenishing material, thereby forming an internal-surface carbon conductive channel. In this way, with carbon nanotubes as the core part, the external carbon material can also participate in the conduction, so that the current can be transmitted through more paths, thereby improving the overall conductivity and capacity. In addition, carbon nanoparticles can stabilize the surface structure of the material. After carbon nanoparticles are coated on the surface of the positive electrode lithium replenishing material, the air sensitivity is reduced. After being placed in the air, the material capacity decreases slowly, and the material phase structure does not change significantly.

[0069] The third aspect of the present application provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode material layer located on at least one side of the positive electrode current collector, wherein the positive electrode material layer comprises the positive electrode lithium replenishing material described in the first aspect of the present application or the positive electrode lithium replenishing material prepared by the method described in the second aspect of the present application. Thus, the positive electrode sheet has good electrical conductivity.

[0070] In some embodiments, the positive electrode current collector may be a metal current collector or a composite current collector. For example, the metal current collector includes but is not limited to an aluminum foil current collector; the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base film. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material base film (such as a base film of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0071] In some embodiments, in addition to the positive electrode lithium replenishing material described above, the positive electrode material layer may also include positive electrode active substances, binders and conductive agents, and additives with specific functions and effects may also be added according to actual needs, such as lithium replenishing agents, film-forming additives, flame retardants, high temperature / low temperature stabilizers, etc.

[0072] In some embodiments, the positive electrode active material may include at least one of a layered structure positive electrode active material (e.g., nickel-cobalt-manganese ternary positive electrode material, nickel-cobalt-aluminum ternary positive electrode material, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich / sodium layered and rock salt phase layered materials), an olivine-type phosphate active material (e.g., lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, etc.), and a spinel structured positive electrode active material (e.g., spinel lithium manganese oxide, spinel lithium nickel manganese oxide, lithium-rich spinel lithium manganese oxide, and lithium nickel manganese oxide, etc.). It is understood that the above-mentioned positive electrode active material may further include doping elements and coating layers, etc.

[0073] As an example, the binder in the positive electrode material layer may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin.

[0074] As an example, the conductive agent in the positive electrode material layer may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0075] The fourth aspect of the present application provides a lithium ion battery, comprising the positive electrode sheet described in the third aspect of the present application. Thus, the lithium ion battery has good conductivity and high available capacity.

[0076] It can be understood that there is no particular limitation on the specific type of the lithium-ion battery, which can be a primary battery or a secondary battery; the shape of the lithium-ion battery can be a cylindrical battery or a square battery, and according to the outer packaging classification, the lithium-ion battery can be a hard shell battery, a soft pack battery, etc.

[0077] It can be understood that, in addition to the positive electrode sheet mentioned above, the lithium-ion battery has the necessary structure and components of a conventional battery, which generally also includes a negative electrode sheet, a separator, an electrolyte and an outer packaging, wherein the positive electrode sheet, the separator and the negative electrode sheet are made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte (including electrolyte, semi-solid electrolyte, solid electrolyte, etc.) are contained in the outer packaging.

[0078] The embodiments of the present application are described in detail below.

[0079] Example 1

[0080] 1. OH - with Fe 2+ Weigh lithium hydroxide and ferric oxide in a molar ratio of 5.5:1, add them to a high-energy ball mill and mill for 12 hours, then sieve through a 200-mesh screen. Put them into a sintering furnace and heat them to 500°C at 2°C / min for 4 hours, then continue to heat them to 900°C at 2°C / min for 20 hours, introduce nitrogen into the furnace during sintering, take them out after cooling, crush them with a crusher, and then sieve them through a 400-mesh screen.

[0081] 2. Take 50g of the lithium iron oxide material prepared in 1 and add it to 100ml of ethanol solution, and add 10g of carbon nanotubes for grinding. The grinding medium is zirconia balls with a particle size of 1mm-3mm. The grinding time is 1h. Finally, the ground mixed slurry is spray dried.

[0082] 3. The spray-dried material and SUPER-P were ball-milled at a mass ratio of 1:0.02, and the mixed material was sintered at 350°C for 4 hours in a nitrogen atmosphere. Finally, a lithium-rich lithium iron oxide positive electrode lithium replenishing material was obtained, in which carbon nanotubes were filled inside the lithium replenishing material and carbon nanoparticles were coated on the surface of the material.

[0083] Example 2

[0084] 1. OH - with Fe 2+ Weigh lithium hydroxide and ferric oxide in a molar ratio of 6:1, add them to a high-energy ball mill and mill for 12 hours, then sieve through a 200-mesh screen. Put them into a sintering furnace and heat them to 600°C at 2°C / min for 4 hours, then continue to heat them to 850°C at 2°C / min for 20 hours. During sintering, introduce nitrogen into the furnace, take them out after cooling, crush them with a crusher, and then sieve through a 400-mesh screen.

[0085] 2. Take 50 g of the lithium iron oxide material prepared in 1 and add it to 100 ml of ethanol solution, and add 15 g of carbon nanotubes for grinding. The grinding medium particle size is 1 mm-3 mm zirconium oxide balls. The grinding time is 1 h. Finally, the ground mixed slurry is spray dried.

[0086] 3. The spray-dried material and SUPER-P were ball-milled at a mass ratio of 1:0.02, and the mixed material was sintered at 350°C for 4 hours in a nitrogen atmosphere. Finally, a lithium-rich lithium iron oxide positive electrode lithium replenishing material was obtained, in which carbon nanotubes were filled inside the lithium replenishing material and carbon nanoparticles were coated on the surface of the material.

[0087] Embodiments 3 to 8

[0088] Same as Example 1, specific differences are shown in Table 1.

[0089] Comparative Example 1

[0090] The difference from Example 1 is that no carbon coating layer is coated on the surface of the positive electrode lithium supplementing material.

[0091] 1. OH - with Fe 2+ Weigh lithium hydroxide and ferric oxide in a molar ratio of 5.5:1, add them to a high-energy ball mill and mill for 12 hours, then sieve through a 200-mesh screen. Put them into a sintering furnace and heat them to 500°C at 2°C / min for 4 hours, then continue to heat them to 900°C at 2°C / min for 20 hours, introduce nitrogen into the furnace during sintering, take them out after cooling, crush them with a crusher, and then sieve them through a 400-mesh screen.

[0092] 2. Take 50g of the lithium iron oxide material prepared in 1 and add it to 100ml of ethanol solution, and add 10g of carbon nanotubes for grinding. The grinding medium is zirconia balls with a particle size of 1mm-3mm. The grinding time is 1h. Finally, the ground mixed slurry is spray dried.

[0093] 3. The spray-dried material was sintered at 350° C. for 4 h in a nitrogen atmosphere to finally obtain a lithium-rich lithium iron oxide positive electrode lithium replenishing material in which carbon nanotubes were filled inside the lithium replenishing material.

[0094] Comparative Example 2

[0095] The difference from Example 1 is that no carbon nanotubes are filled inside the positive electrode lithium supplement material.

[0096] 1. OH - with Fe 2+ Weigh lithium hydroxide and ferric oxide in a molar ratio of 5.5:1, add them to a high-energy ball mill and mill for 12 hours, then sieve through a 200-mesh screen. Put them into a sintering furnace and heat them to 500°C at 2°C / min for 4 hours, then continue to heat them to 900°C at 2°C / min for 20 hours, introduce nitrogen into the furnace during sintering, take them out after cooling, crush them with a crusher, and then sieve them through a 400-mesh screen.

[0097] 2. The lithium iron oxide material prepared in step 1 and SUPER-P were ball-milled at a mass ratio of 1:0.02, and the mixed material was sintered at 350°C for 4 hours in a nitrogen atmosphere. Finally, a lithium iron oxide positive electrode material with carbon nanoparticles coated on the surface of the material was obtained.

[0098] Comparative Example 3

[0099] The difference from Example 1 is that no carbon nanotubes are filled in the positive electrode lithium replenishing material, and no carbon coating layer is coated on the surface of the positive electrode lithium replenishing material.

[0100] 1. OH - with Fe 2+ Weigh lithium hydroxide and ferric oxide in a molar ratio of 5.5:1, add them to a high-energy ball mill and mill for 12 hours, then sieve through a 200-mesh screen. Put them into a sintering furnace and heat them to 500°C at 2°C / min for 4 hours, then continue to heat them to 900°C at 2°C / min for 20 hours, introduce nitrogen into the furnace during sintering, take them out after cooling, crush them with a crusher, and then sieve them through a 400-mesh screen.

[0101] Table 1

[0102]

[0103] Test method:

[0104] First charge specific capacity: The positive electrode lithium replenishing material prepared in each embodiment and comparative example is dispersed in NMP with a binder PVDF and a conductive agent SUPER-P at a mass ratio of 8:1:1, dispersed in a homogenizer, defoamed, etc., coated on aluminum foil, and vacuum dried to obtain a positive electrode plate; then button-type 2032 batteries are assembled in a glove box, the electrolyte is 1.2 mol / L LiPF6, wherein the solvent volume ratio is EC:EMC=3:7, the diaphragm is a Celgard polypropylene film, and a metal lithium sheet is used as the counter electrode. The assembled half-battery is subjected to a capacity test on a Xinwei tester, and the specific steps are as follows: charge to 4.3V at a constant current and constant voltage of 0.05C, and the cut-off current is 0.02C to obtain the first charge specific capacity of the positive electrode lithium replenishing material. The test results are shown in Table 2, and the charging curves of the batteries prepared from the positive electrode lithium replenishing materials in Examples 1, 4 and the comparative example are shown in Table 2. Figure 1 , Figure 2 and Figure 3 .

[0105] D50 particle size: The positive electrode material is dispersed in methanol solvent, and after ultrasonic dispersion, it is tested using a laser particle size analyzer.

[0106] Carbon coating thickness: tested using a transmission scanning electron microscope.

[0107] Test results:

[0108] Table 2

[0109]

[0110] It can be seen from the test data in Table 2 that the first charge specific capacity of the lithium-supplementing positive electrode material of the embodiment of the present application is significantly better than that of the comparative example, indicating that the positive electrode lithium-supplementing additive of the present application has a better lithium-supplementing effect, effectively reduces the lithium-depletion potential, improves the conductivity and lithium-ion conductivity of the lithium-supplementing material, and improves the lithium-depletion kinetics. Specifically, by comparing Examples 1 and 2, and Examples 3 and 4, it can be seen that within a suitable range, the D50 particle size is relatively large, which is conducive to improving the performance of the lithium-supplementing material; by comparing the embodiments and the comparative examples, it can be seen that the conductivity and lithium-ion conductivity of the lithium-supplementing material of the lithium-supplementing material are not significantly improved by performing carbon nanotube filling and carbon coating alone inside, thereby improving the specific capacity; it indicates that performing carbon nanotube filling and carbon coating simultaneously can effectively form an internal-surface carbon conductive channel, thereby improving the overall conductivity and capacity.

[0111] In summary, it is shown that the positive electrode lithium supplement material of the present application has a higher capacity and better conductivity, which is beneficial to improving the electrochemical performance of the battery using the positive electrode lithium supplement material.

[0112] In the description of the present application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0113] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0114] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A positive electrode lithium supplement material, characterized in that: include: A core, comprising a lithium-supplemented matrix and carbon nanotubes, wherein the carbon nanotubes are dispersed in the lithium-supplemented matrix; A carbon coating layer is coated on at least a portion of the surface of the core.

2. The positive electrode lithium supplement material according to claim 1, characterized in that: The carbon nanotubes are uniformly distributed in the lithium supplement matrix.

3. The positive electrode lithium supplement material according to claim 1, characterized in that: The thickness of the carbon coating layer is 5nm-10nm.

4. The positive electrode lithium supplement material according to claim 1, characterized in that: The carbon coating layer includes carbon nanoparticles.

5. The positive electrode lithium supplement material according to claim 1, characterized in that: The lithium-supplemented matrix includes Li2NiO2, Li2MoO3, Li5Fe 0.9 Al 0.1 O4, Li6MnO4, Li6Mn 0.5 Ru 0.5 At least one of O4, Li5FeO4, Li6CoO4, and Li3N.

6. The positive electrode lithium supplement material according to claim 1, characterized in that: The mass ratio of the lithium supplement matrix to the carbon nanotubes is 1:0.01-0.

5.

7. The positive electrode lithium supplement material according to claim 1, characterized in that: The D50 particle size of the positive electrode lithium supplement material is 6 μm to 15 μm.

8. A method for preparing a positive electrode lithium supplement material, characterized in that: include: mixing the lithium-supplemented matrix and the carbon nanotubes to obtain a core precursor; The core precursor is mixed with a carbon source and subjected to a first sintering process under a protective atmosphere to obtain the positive electrode lithium supplement material; The positive electrode lithium supplement material comprises a core and a carbon coating layer, wherein the core comprises a lithium supplement matrix and carbon nanotubes dispersed in the lithium supplement matrix, and the carbon coating layer is coated on at least a portion of the surface of the core.

9. The method according to claim 8, characterized in that The preparation of the core precursor comprises: Before mixing the lithium-supplemented matrix with carbon nanotubes, the lithium-supplemented matrix is ​​first ground.

10. The method according to claim 8 or 9, characterized in that: The preparation of the core precursor comprises: The lithium-supplemented matrix, carbon nanotubes and solvent are mixed, and the obtained mixture is subjected to a second grinding to obtain a mixed slurry; The mixed slurry is spray-dried to obtain the core precursor.

11. The method according to claim 10, characterized in that The solvent includes at least one of ethanol, methanol and ethylene glycol.

12. The method according to claim 8, characterized in that The carbon source includes at least one of sucrose, glucose, SUPER-P, KS-6, KS-15, VGCF, and SFG6.

13. The method according to claim 8, characterized in that The core and the carbon source are mixed in a mass ratio of 1:0.01 to 0.

5.

14. The method according to claim 8, characterized in that The first sintering satisfies at least one of the following conditions: The first sintering atmosphere is a nitrogen atmosphere; The first sintering temperature is 350°C to 500°C; The first sintering time is 2 hours to 5 hours.

15. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode material layer located on at least one side of the positive electrode current collector, wherein the positive electrode material layer comprises the positive electrode lithium replenishing material according to any one of claims 1 to 7 or the positive electrode lithium replenishing material prepared by the method according to any one of claims 8 to 14.

16. A lithium ion battery, characterized in that: The invention comprises the positive electrode lithium replenishing material according to any one of claims 1 to 7, the positive electrode lithium replenishing material prepared by the method according to any one of claims 8 to 14, or the positive electrode sheet according to claim 15.

Citation Information

Patent Citations

  • Positive pole piece, preparation method thereof and lithium ion battery

    CN119050262A